Bidirectional ocular dominance plasticity of inhibitory networks: recent advances and unresolved questions - Smith, Gordon B.; Bear, Mark F. (Frontiers in Cellular Neuroscience, 2010)
Monocular visual deprivation (MD) produces profound changes in the ocular dominance (OD) of neurons in the visual cortex. MD shifts visually evoked responses away from the deprived eye and towards domination by the open eye. Over thirty years ago, two different theories were proposed to account for these changes: either through effects on excitatory visual drive, thereby shifting the balance of excitation in favor of the open eye, or through effects on intracortical inhibition, thereby suppressing responses from the deprived eye. In the intervening years, a scientific consensus emerged that the major functional effects of MD result from plasticity at excitatory connections in the visual cortex. A recent study by Yazaki-Sugiyama and colleagues in mouse visual cortex appears to re-open the debate. Here we take a critical look at these intriguing new data in the context of other recent findings in rodent visual cortex.